2021
DOI: 10.1128/msphere.01298-20
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Nucleocytoplasmic Large DNA Virus and Host Interactions Predicted by Co-occurrence Analyses

Abstract: Nucleocytoplasmic large DNA viruses (NCLDVs) are highly diverse and abundant in marine environments. However, the knowledge of their hosts is limited because only a few NCLDVs have been isolated so far. Taking advantage of the recent large-scale marine metagenomics census, in silico host prediction approaches are expected to fill the gap and further expand our knowledge of virus-host relationships for unknown NCLDVs. In this study, we built co-occurrence networks of NCLDVs and eukaryotic taxa to predict virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Additionally, viruses have been proposed as a key factor influencing the protist communities as they can impose top–down controls on their specific host populations (Nagasaki et al 1994; Brussaard et al 1996). Recent studies using Mantel statistics or co‐occurrence network analysis indicated that Imitervirales are tightly associated with a variety of protist lineages at a global level (Endo et al 2020; Meng et al 2021), although only little of them have been isolated (Mihara et al 2018). Our 18S rDNA barcoding revealed that chlorophytes and haptophytes, both of which are known host lineages of Imitervirales , were major protists in the small‐size fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, viruses have been proposed as a key factor influencing the protist communities as they can impose top–down controls on their specific host populations (Nagasaki et al 1994; Brussaard et al 1996). Recent studies using Mantel statistics or co‐occurrence network analysis indicated that Imitervirales are tightly associated with a variety of protist lineages at a global level (Endo et al 2020; Meng et al 2021), although only little of them have been isolated (Mihara et al 2018). Our 18S rDNA barcoding revealed that chlorophytes and haptophytes, both of which are known host lineages of Imitervirales , were major protists in the small‐size fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Our 18S rDNA barcoding revealed that chlorophytes and haptophytes, both of which are known host lineages of Imitervirales, were major protists in the small-size fraction. Although the dominating clades in the large-sized eukaryotic communities such as dinoflagellates, ciliophora, and diatoms have not yet been reported as host lineages, these groups were predicted to be the most closely linked host group for Imitervirales from a global scale network analysis (Meng et al 2021). To date, some diatoms are known to be infected by smaller ssDNA and ssRNA viruses (Toyoda et al 2012), and a dinoflagellate Heterocapsa circularisquama can be infected by ssRNA viruses and viruses of Asfarviridae, another clade of NCLDV (undefined Nagasaki et al 2006).…”
Section: Tight Association Between Imitervirales and The Microbial Eu...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though these metagenomes assembled viral genomes were of estimated high completeness and low contamination, their hosts and the capacity of each virus to have multiple hosts often remain elusive. Co-occurrence study in Tara Oceans tried to identify probable hosts but their analyses identified families of virus with their probable host in Eukaryotes such as the dominance of Mimiviridae in relation with Alveolata, Opisthokonta, Rhizaria, and Stramenopiles (Meng et al, 2021). Further, based on detection of horizontal gene transfer events in members of the Klosneuvirinae have been suggested to infect Anthoathecata, fungi, arthropods, and various protists including slime molds (Schulz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Giant viruses often encode complex functional repertoires in their genomes that include tRNA synthetases, rhodopsins, cytoskeletal components, histones, and proteins involved in glycolysis, the TCA cycle, and other aspects of central carbon metabolism (Aylward et al .). Recent studies have shown that giant viruses are widespread in the environment and infect a wide range of eukaryotic hosts, including green algae (Schulz et al ., 2020; Moniruzzaman et al ., 2020a; Endo et al ., 2020; Meng et al ., 2021). The complex genomes of giant viruses coupled with their collectively broad host range and ability to endogenize into the genomes of their hosts provides compelling evidence that they may be important vectors of gene transfer in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%